Comparing numerical methods for response of beams with moving mass - Bulut, Hasan; Kelesoglu, Omer (Elsevier Sci Ltd, 2010)
In this paper, we applied two methods to solve a class of linear differential equation with initial conditions using Adomian's decomposition and homotopy perturbation methods. We present analytical-numerical methods that can be used to determine the dynamic behaviour of beams, with different boundary conditions, carrying a moving mass. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Adomian decomposition method (ADM); Homotopy perturbation method (RPM); Moving mass; Adomian polynomial; Linear differential equation; Parabolic equation